PENGUJIAN KARAKTERISTIK KINERJA SIKLON SEPARATOR HEMAT ENERGI - Prihadi Setyo Darmanto; Katon Primanto (Mesin, 1997)
The performance of cyclone separator is measured by its capability to separate solid particles from dust laden gas ï¬‚ow and its pressure drop. The last parameter shows the energy used for running it. The cyclone having highest separation efficiency and lowest pressure drop is needed in the industrial application. It is the aim of this research work to study a modiï¬ed cyclone in order to ï¬nd a better performance than the classical cyclone type. The modiï¬cation is employed by inclining the roof of cyclone. With this modiï¬cation, the pressure drop could be reduced of about 50% without signiï¬cantly reducing of separation efficiency. This paper presents an investigation of performance of the modiï¬ed cyclone. This experiment proposes some empirical correlation of separation eï¬‚iciency and pressure drop at various values of dust load.